Optimal fiscal policy when migration is feasible - Filippo Occhino (Rutgers University, Department of Economics, 2005)
This paper investigates how the feasibility of migration affects governments' optimal fiscal policies. We assume that households migrate towards economies where their welfare is higher, governments choose taxes and public expenditures to maximize a weighted sum of the households' welfare, welfare is increasing in public expenditures, and only distortionary labor income taxes are available. In isolated economies, the optimal fiscal policy implies that some households are net fiscal contributors, while other households are net fiscal beneficiaries. When households can migrate, however, governments compete for the households which are net fiscal contributors, and modify the fiscal policy in their favor, lowering their taxes and net fiscal contribution, and increasing their welfare. The magnitude of the effect increases with the sensitivity of migration to welfare. In the limiting case of free mobility, all households are zero net fiscal contributors.
Keywords: E62; 330; Optimal fiscal policy; Ramsey equilibrium; Migration; Fiscal competition; Mobility; Fiscal burden